HUBUNGAN KEPUASAN PELAYANAN MAKANAN DENGAN TINGKAT KECUKUPAN ENERGI DAN PROTEIN PASIEN DI RUMAH SAKIT UNIVERSITAS AIRLANGGA SURABAYA - Amanda Nurqisthy; Merryana Adriani; Lailatul Muniroh (Media Gizi Indonesia, 2016)
Patient’s satisfaction is one of success indicator of hospital food service, which affect the level of energy and protein sufficiency of patients. The aim of this study was to analyze the relationship between food service satisfaction and energy and protein suffi ciency level of patients in Universitas Airlangga Hospital. Thirty-four samples who receive High Energy and Protein diet were chosen using purposive sampling. Patient satisfaction data was collected through interview using a questionnaire and food waste was analyze through observation by Comstock method. Data was processed using chi square test. The result showed that level of energy and protein suffi ciency of most patients are adequate (73.5% and 70.6%) and most patient are satisfi ed with the hospital food service (76.5%). There was a relationship between satisfaction of food service with the level of energy and protein suffi ciency of patients (p = 0.017 and p = 0.031). Patients who were satisfi ed with the food services of hospital has a suffi cient intake of energy and protein. It is needed to restore system of food operation in hospital, especially on the punctuality of food distributionand fl avor of food, considering that those indicator, were source of dissatisfaction.Keywords: food service satisfaction, patients, the level of energy and protein suffi ciency